The Arab Middle East and Religious Authority in Indonesia - Nico Kaptein (Tebuireng: Journal of Islamic Studies and Society, 2020)
This publication presents a broad overview of the religious relations between the Arab Middle East and Indonesia over roughly the last five hundred years. It shows that the Middle East has always held and continues to hold an extremely important place in Islamic life in Indonesia, but that, especially since independence, Middle Eastern Islam is being engaged with more critically, and that Salafism and other intolerant and radical forms of Islam from the Middle East are being combatted on an ideological level by propagating the specific Indonesian understanding of Islam, called Islam Nusantara.